MATERNAL ANXIETY DURING THE COVID-19 PANDEMIC CAUSES NON-COMPLIANCE WITH MEASLES IMMUNIZATION IN THE WORK AREA PUSKESMAS DARUSSALAM, ACEH BESAR REGENCY - Thursina, Indah; Idiana, Adri; Putri, Isnaini (Journal of Midwifery and Community Health (JMCH), 2023)
Background: Measles immunization coverage during the COVID-19 period has decreased. The COVID-19 pandemic, which is more focused on preventing the spread of the virus, has resulted in disrupted immunization services. Many factors cause a decrease in measles immunization in children, one of which is maternal anxiety during the COVID-19 period. Method: This study used a cross-sectional study design in 86 mothers who had babies aged 9-12 months. Sampling is carried out by two-stage sampling. Data collection used a COVID-19 anxiety scale questionnaire (CAS) and MCH book recording to determine measles immunization records. Data analysis using chi-square test. Result: The number of mothers who are anxious about Covid-19 is more disobedient in the administration of measles immunization (69.1) than those who are compliant (30.9). There is a relationship between maternal anxiety during COVID-19 and adherence to measles immunization (p-value 0.026). Conclusion: Maternal anxiety during the COVID-19 period is related to compliance with measles immunization in the work area of the Darussalam Health Center, Aceh Besar Regency. Increased understanding related to the prevention and transmission of COVID-19 must be done to the community. This effort is made to reduce the level of anxiety of the people.